2014
DOI: 10.2146/ajhp130601
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin use in pediatric patients

Abstract: Due to the limited nature of the available literature, use of daptomycin in pediatric patients should be limited to situations in which other options are not viable due to toxicity, local susceptibility patterns, or likely treatment failure. As a result of faster drug CL and lower AUC values, higher doses may be necessary in pediatric patients to achieve serum concentrations similar to those seen with adult dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…Methicillin-resistant S. aureus (MRSA) has emerged as a common pathogen in both healthcare and community-acquired infections [ 7 , 8 ]. Community-acquired MRSA has been found to be particularly responsible for causing IE in patients with human immunodeficiency virus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant S. aureus (MRSA) has emerged as a common pathogen in both healthcare and community-acquired infections [ 7 , 8 ]. Community-acquired MRSA has been found to be particularly responsible for causing IE in patients with human immunodeficiency virus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Limited pharmacokinetic studies have manifested faster daptomycin clearance in children and it seems to have a shorter half-life in children aged 2-6 when compared to children aged 12-17. 10 Higher doses may be required in younger patients and the administration of 15 mg/kg/12 h was reported as a maximum dose in the literature in an infant. 2,8 Our patient was treated at a dose of 8 mg/kg/ Serum CPK levels were in normal limits during the treatment.…”
Section: Case Reportmentioning
confidence: 99%
“…However, production of toxic compounds by some of these bacteria raises concerns about the safety of these isolates in food production (Camargo et al., ; Choi & Woo, ; Franz et al., ). Additionally, several studies reported that enterococci can transfer resistance to even more virulent bacteria, such as Staphylococcus aureus (Bellanger et al., ; Durand, Brueckner, Sampadian, Willett, & Belliveau, ). Hence, the ability of enterococci to act as reservoirs of antibiotic resistance genes within the food chain poses an important food safety risk (Delpech et al., ; Gousia, Economou, Bozidis, & Papadopoulou, ; Jahan, Krause, & Holley, ; Pesavento, Calonico, Ducci, Magnanini, & Lo Nostro, ; Stensland et al., ).…”
Section: Introductionmentioning
confidence: 99%